About of the constitutional demise of Czechoslovakia - Klíma, Karel (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The situation after the elections of 1992 showed that an ordinary federation was probably an invincible barrier for the future constitutional development. Public opinion did not accept the idea of the division of the Czechoslovakia. The dissolution of Czechoslovakia resulted from an objective situation generated by the elections and escalated with the non compromising ambitions of the winning coalitions in both countries. Constitutional curiosity of the situation of the Czechslovakia consisted in the conflict beetwen federal consitution and new Slovak constitutional system (since 1.10.1992) when each of these declared its supremacy.